2005
DOI: 10.1161/01.str.0000165926.74213.e3
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Stroke Risk Is Higher Than Cardiac Event Risk After Initial Stroke/Transient Ischemic Attack

Abstract: Background and Purpose-Patients with ischemic stroke and transient ischemic attack (TIA) are at risk for recurrent cerebrovascular and cardiac events. Understanding which of these adverse events is more likely to occur next is instructive for preventive therapy planning. Comparison between cardiac and stroke as secondary events were made using cumulative incidence estimates. Results-Over the follow-up period, 172 patients had a cardiac event (62.8% MI, 7.6% CABG, 14.5% PTCA, 9.3% MI and PTCA, and 5.8% MI and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 14 publications
2
50
1
Order By: Relevance
“…Past studies have found a 1-year recurrence rate for stroke of <14%. [44][45][46] The strengths of our study include the use of spatial statistics to identify and monitor county clusters of stroke hospitalization rates, the identification of transitional counties in addition to persistently high-and persistently low-rate clusters, and the inclusion of community-level healthcare profiles and socioeconomic profiles. The use of Medicare data enabled nationwide analysis of geographic patterns in stroke hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have found a 1-year recurrence rate for stroke of <14%. [44][45][46] The strengths of our study include the use of spatial statistics to identify and monitor county clusters of stroke hospitalization rates, the identification of transitional counties in addition to persistently high-and persistently low-rate clusters, and the inclusion of community-level healthcare profiles and socioeconomic profiles. The use of Medicare data enabled nationwide analysis of geographic patterns in stroke hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…8 The observation that ischemic stroke patients have additional costs and resource use for non-stroke-related cardiovascular events, such as MI and coronary heart disease (CHD), in addition to strokerelated events, supports the notion that stroke patients are at high risk of future coronary events as well as recurrent cerebrovascular events. [2][3][4][5][6][7] Therefore, therapeutic strategies aimed at total cardiovascular risk reduction in stroke patients may have the potential to reduce both the morbidity and mortality associated with stroke as well as downstream hospitalizations and health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…8 In a study of cardiovascular events among Michigan Medicare patients after stroke or TIA, the 2-year incidence of stroke was 11.8%, whereas the incidence of cardiac events (such as PCI and coronary bypass procedures, as well as MI) was 7.7%. 9 Another study of recurrent events after first ischemic stroke among elderly patients enrolled in the Heart Protection Study (age 65 years or older) found that the 1-year rate of recurrent stroke was nearly twice that of cardiac events (105.4 versus 59.3 per thousand person-years, respectively). 10 Similar patterns of recurrent events have also been described in clinical intervention studies.…”
Section: Differences Between Recurrent Cerebrovascular and Coronary Ementioning
confidence: 99%